Dorsal Root Ganglion Stimulation Lead Fracture Within the Superficial Fascial Layers in 4 Cases. Issue 11 (September 2020) - Chapman, Kenneth B.; Patel, Kiran V.; van Helmond, Noud; Chien, George C. Chang
Abstract : We present 4 cases of dorsal root ganglion stimulation lead fracture. In these cases, the surgical technique involved (1) traversing fascial layers for placement of leads via a Tuohy needle in the upper low back, (2) subcutaneous tunneling from the implantable pulse generator site to the lead puncture site without dissecting below the superficial fascial plane at the puncture site, and (3) connection of the lead/extension with the generator. All fractures occurred adjacent to the original lead puncture site. These cases suggest lead entrapment within the membranous fascial plane, with tension on a thin lead, is a mechanism underlying lead fracture.